Method for degrading organic pollutants by activating peracetic acid by using manganese metal doped crystalline carbon nitride catalyst
The activation of peracetic acid by doping the crystalline carbon nitride catalyst by manganese metal is solved, and the problem of difficulty in efficiently removing organic pollutants in the water environment in the prior art is solved, and an efficient and economical degradation effect of organic pollutants is achieved.
Patent Information
- Application Number
- CN202510030204.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art is difficult to efficiently remove organic pollutants such as fluoroquinolones (FQs) in water environments, and traditional methods have problems such as large catalyst usage, high cost and low treatment efficiency.
Peracetic acid is activated by using manganese metal doped crystalline carbon nitride catalyst, and the efficient activation of the catalyst forms highly active substances, thereby efficiently oxidizing and decomposing organic pollutants.
The degradation of organic pollutants such as fluoroquinolone drugs is achieved at a low amount of catalyst, low cost, high treatment efficiency and good removal effect is achieved. Especially at 25°C and a pH value of 7.0, the degradation rate of organic pollutants such as fluoroquinolone drugs reaches 100%, 97.9%, 94.3%, and 98.1%.
Smart Images

Figure CN119612744A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of environmental functional material preparation and water environment protection, and relates to a method for degrading organic pollutants by activating peracetic acid using a manganese metal-doped crystalline carbon nitride catalyst. Background Art
[0002] With the continuous development of industrial technology, the harm caused by organic pollutants to the environment has received attention. Among them, antibiotics and other drugs have become important drugs for the prevention and treatment of diseases. However, a large number of unused or expired antibiotics often enter the ecological environment directly without undergoing special treatment and disposal processes, which has caused serious harm to the environment and human health. For example, fluoroquinolone antibiotics (FQs), a commonly used antibiotic for human and veterinary use, have been widely detected in the aquatic ecological environment. FQs are toxic to aquatic organisms such as bacteria, algae, invertebrates and fish. At the same time, FQs have bioaccumulation and weak biodegradability, making them easy to accumulate in the human body. Fluoroquinolone drug pollution poses a great threat to human health and ecological environment safety. However, the existing sewage treatment technology is not ideal for removing FQs and cannot meet the requirements of related risk treatment. Therefore, there is an urgent need to develop a fast and efficient method to remove organic pollutants in the water environment.
[0003] In recent years, for FQs pollution treatment, traditional methods such as adsorption and biological treatment cannot completely remove FQs in water, and there is a risk of secondary pollution. Advanced oxidation processes (AOPs) can generate highly active substances in situ, such as SO 4 2- , ·OH, etc., can efficiently oxidize and remove FQs, completely mineralize them or convert them into low-toxic substances, and have attracted widespread attention as an environmentally friendly and low-cost technology. Common oxidants include peroxymonosulfate (PMS), peroxydisulfate (PDS), ozone (O 3 ), hydrogen peroxide (H 2 O 2 ) and peracetic acid (PAA), etc. At the same time, compared with other peroxides, PAA has more advantages, such as PAA can be used as a disinfectant, and PAA is less dependent on pH changes. After being activated, it can produce a large number of active substances and many small molecule carbon sources, with higher bioavailability, low toxicity and few by-products. However, PAA itself cannot directly degrade pollutants. Additional ultraviolet light or homogeneous and heterogeneous catalysts can effectively activate PAA to generate highly active species. At the same time, compared with high energy input ultraviolet light, using catalysts to activate PAA is more cost-effective. Therefore, it is necessary to develop new catalysts with high selectivity and PAA activation activity.
[0004] Graphitic carbon nitride (gC3 N 4 ) is a unique catalytic material that has been widely studied in water and wastewater treatment in recent years due to its stable structure and cost-effectiveness. Although inexpensive polymer graphitic carbon nitride is a promising catalyst, its amorphous and disordered structure hinders the transfer of electrons. The hydrogen bonds of the original graphitic carbon nitride monomers exist in the covalent framework, which may hinder the shuttling of electrons on the plane, resulting in low conductivity. To address these problems, new methods for synthesizing crystalline carbon nitride with a highly ordered structure have received widespread attention. The high polymerization of tri-s-triazine units in crystalline carbon nitride provides a smooth channel for the migration of electrons in the π-conjugated framework, and the crystallinity plays a vital role in regulating the electronic structure and electron migration behavior. However, existing crystalline carbon nitride is mainly prepared by molten salt method, solid salt method, ion thermal method, solvent thermal method and other methods, and generally still has defects such as poor crystallinity, few active sites, and easy agglomeration, making it difficult to achieve efficient activation of peracetic acid, and thus difficult to quickly degrade organic pollutants. In addition, the molten salt added during the synthesis process can easily destroy the original monomer structure of carbon nitride, thereby changing the properties of carbon nitride. In particular, when preparing crystalline carbon nitride by the molten salt method, it is necessary to operate in a glove box, and the process is complicated. In addition, the molten salt method requires a large amount of salt, such as LiCl, LiBr, KCl, etc. as a structure directing agent, which not only has a low yield but also has limited applications. In addition, in order to improve the crystallinity of graphite phase carbon nitride, some researchers have proposed a method of inducing high crystalline carbon nitride by doping with polyvinyl pyrrolidone (PVP). By destroying the hydrogen bonds of carbon nitride, high crystalline carbon nitride is prepared. Obviously, this method is easy to introduce other elements, easy to destroy the original monomer structure of carbon nitride, and change the properties of carbon nitride. The more prominent problem is that the large-scale use of polyvinyl pyrrolidone (PVP) and organic solvents will not only increase the preparation cost, but also easily bring secondary environmental pollution. In addition, in order to increase the active sites of graphite phase carbon nitride, some researchers have proposed a strategy of metal doping of graphite phase carbon nitride. For example, doping graphite phase carbon nitride with iron or nickel can increase the number of active sites on the surface of graphite phase carbon nitride. However, these iron or nickel-doped graphite phase carbon nitrides still have defects such as poor selectivity and catalytic activity for PAA, and it is difficult to efficiently activate PAA under the premise of a small amount of catalyst, and thus it is difficult to efficiently and thoroughly degrade organic pollutants.
[0005] Therefore, obtaining a graphite-phase carbon nitride catalyst with multiple active sites, high catalytic activity and good stability is of great significance for highly selective and efficient activation of PAA and achieving efficient degradation of organic pollutants. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a method for degrading organic pollutants by activating peracetic acid using a manganese metal-doped crystalline carbon nitride catalyst, which has the advantages of low catalyst usage, low cost, high treatment efficiency, good removal effect, and is green and environmentally friendly.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0008] A method for degrading organic pollutants by activating peracetic acid using a manganese metal-doped crystalline carbon nitride catalyst, wherein the method uses the manganese metal-doped crystalline carbon nitride catalyst as a catalyst for activating peracetic acid to degrade the organic pollutants; the manganese metal-doped crystalline carbon nitride catalyst comprises crystalline carbon nitride, and the crystalline carbon nitride is doped with a manganese metal element.
[0009] The above method is further improved, wherein the doping amount of manganese metal element in the manganese metal-doped crystalline carbon nitride catalyst is 1.13% to 4.87%; and the crystalline carbon nitride is a flower-shaped nanosheet.
[0010] The above method is further improved, and the preparation method of the manganese metal-doped crystalline carbon nitride catalyst comprises the following steps:
[0011] S1, using a nitrogen precursor as a raw material to carry out a polycondensation reaction to obtain amorphous carbon nitride;
[0012] S2, pyrolyzing the amorphous carbon nitride obtained in step S1 to obtain crystalline carbon nitride;
[0013] S3, grinding and mixing the crystalline carbon nitride and the manganese source obtained in step S2, and then calcining them to obtain a manganese metal-doped crystalline carbon nitride catalyst.
[0014] The above method is further improved, in step S3, the mass ratio of the manganese source to the crystalline carbon nitride is 0.05-0.2:1.
[0015] The above method is further improved, in step S3, the mass ratio of the manganese source to the crystalline carbon nitride is 0.1-0.2:1; and the manganese source is manganese chloride.
[0016] The above method is further improved, in step S1, the nitrogen precursor is at least one of dicyandiamide, melamine, and urea; the polycondensation reaction is carried out under a protective atmosphere; the protective atmosphere is air or nitrogen; the heating rate during the polycondensation reaction is 2°C / min to 10°C / min; the polycondensation reaction is carried out at a temperature of 500°C to 600°C; and the polycondensation reaction time is 4h to 6h.
[0017] The above method is further improved, in step S2, the pyrolysis treatment is carried out under a protective atmosphere; the protective atmosphere is nitrogen; the heating rate during the pyrolysis treatment is 2°C / min to 10°C / min; the pyrolysis treatment is carried out at a temperature of 500°C to 700°C; and the pyrolysis treatment time is 2h to 4h.
[0018] The above method is further improved, in step S3, the calcination is carried out under a protective atmosphere; the protective atmosphere is nitrogen; the heating rate during the calcination is 2°C / min to 10°C / min; the calcination temperature is 500°C to 600°C; the calcination time is 4h to 6h.
[0019] The above method is further improved by using a manganese metal-doped crystalline carbon nitride catalyst as a catalyst for activating peracetic acid to degrade organic pollutants in water.
[0020] The above method is further improved, and when the organic pollutants in the water body are degraded using a manganese metal-doped crystalline carbon nitride catalyst as a catalyst for activating peracetic acid, the method comprises the following steps: mixing the manganese metal-doped crystalline carbon nitride catalyst and organic pollutant wastewater, adding peracetic acid to carry out a degradation reaction, and completing the degradation of the organic pollutants in the wastewater; the amount of the manganese metal-doped crystalline carbon nitride catalyst added is 0.05g to 0.1g per liter of organic pollutant wastewater; the amount of the peracetic acid added is 0.05mmol to 0.1mmol per liter of organic pollutant wastewater.
[0021] The above method is further improved, wherein the organic pollutants in the organic pollutant wastewater are antibiotics or naproxen drugs; the antibiotics are fluoroquinolone drugs; the fluoroquinolone drugs are at least one of enrofloxacin, norfloxacin, ofloxacin, and ciprofloxacin; the initial concentration of organic pollutants in the organic pollutant wastewater is 2 mg / L to 5 mg / L; and the pH value of the organic pollutant wastewater is 5.0 to 7.0.
[0022] The above method is further improved in that the degradation reaction is carried out at a temperature of 25°C to 30°C; and the degradation reaction time is 3min to 10min.
[0023] Compared with the prior art, the advantages of the present invention are:
[0024] (1) In view of the shortcomings of graphite phase carbon nitride catalysts such as low crystallinity, small number of active sites, poor catalytic activity, and poor stability, as well as the resulting defects that graphite phase carbon nitride catalysts are difficult to efficiently activate peracetic acid and difficult to efficiently degrade organic pollutants under conditions of low catalyst dosage, the present invention creatively proposes a method for degrading organic pollutants by activating peracetic acid using a manganese metal-doped crystalline carbon nitride catalyst, wherein the manganese metal-doped crystalline carbon nitride catalyst is used as a catalyst for activating peracetic acid to degrade organic pollutants, wherein the manganese metal-doped crystalline carbon nitride catalyst includes crystalline carbon nitride, and the crystalline carbon nitride is doped with manganese metal elements. Compared with conventional graphite-phase carbon nitride, the crystalline carbon nitride used in the present invention has the following advantages: (a) crystalline carbon nitride has a flower-like nanosheet morphology and a rich pore structure, a large specific surface area, and many active sites, which is not only conducive to the adsorption and activation of peracetic acid, but also conducive to the adsorption and degradation of target pollutants; (b) crystalline carbon nitride has an ordered crystal structure and high crystallinity, which is conducive to the formation of a selective Fenton-like system dominated by surface-mediated electron transfer, and has high selectivity for peracetic acid; (c) crystalline carbon nitride has six long electron-pair nitrogen sites, and the rich electronegative nitrogen sites in the highly ordered structure can provide an ideal ring for the coordination of manganese metal atoms. The environment allows manganese metal atoms to be evenly anchored on the carbon nitride framework, which not only increases the number of active sites on the carbon nitride surface, which is beneficial to improving the catalytic activity, but also enables the manganese active sites to be evenly distributed on the carbon nitride surface, which is beneficial to improving the activation efficiency. On this basis, manganese metal elements are doped into the crystalline carbon nitride. On the one hand, the low electronegativity of manganese metal atoms can be used to promote the carbon nitride to lose electrons, which is beneficial to the activation of the coordinated atoms in the carbon nitride. On the other hand, the doping of manganese metal atoms can also regulate the electronic structure of carbon nitride and promote the transfer of electrons inside carbon nitride, ultimately making the carbon nitride catalyst have higher catalytic activity. In the present invention, under the joint action of crystalline carbon nitride and manganese metal element, the manganese metal doped crystalline carbon nitride catalyst has higher crystallinity, more active sites and higher catalytic activity, so when it is used as a catalyst for activating peracetic acid, it can achieve efficient activation of peracetic acid and quickly form a large amount of highly active substances, and then these highly active substances can be used to efficiently oxidize and decompose organic pollutants, thereby achieving efficient degradation of organic pollutants. Taking fluoroquinolone drugs as an example, under the conditions of 25°C and an initial solution pH value of 7.0, only 5 mg of catalyst and 0.08 mmol of peracetic acid need to be added to degrade 100 mL, 2 mg / L enrofloxacin, norfloxacin, ofloxacin and ciprofloxacin aqueous solutions by 100%, 97.9%, 94.3% and 98.1% within 6 minutes.The method of the present invention utilizes a manganese metal-doped crystalline carbon nitride catalyst to activate peracetic acid to degrade organic pollutants, has the advantages of small catalyst dosage, low cost, high treatment efficiency, good removal effect, green environmental protection, etc., and is of great significance for effectively removing organic pollutants in the environment.
[0025] (2) In the present invention, the crystalline carbon nitride used is a nitrogen precursor (such as dicyandiamide) as a raw material, and the hydrogen bonds formed in the carbon nitride skeleton are destroyed by a two-step heat treatment method, thereby preparing a high-crystallinity carbon nitride, which solves the problem of low crystallinity of carbon nitride in the traditional synthesis method, and no molten salt is added during the synthesis process, no additional elements are introduced, the original monomer structure of carbon nitride is not destroyed, and the properties of carbon nitride are not changed. At the same time, in the absence of any additives, toxic solvents or pre-intercalation steps, the yield of crystalline carbon nitride can be improved. The present invention can prepare a high-crystallinity carbon nitride catalyst through a simple heat treatment method, and has the advantages of low material price, simple process, easy operation, easy large-scale preparation and industrial production, etc., and provides method support for the subsequent large-scale preparation of Fenton-like materials for efficient treatment of complex organic wastewater.
[0026] (3) In the present invention, by optimizing the mass ratio of manganese source to crystalline carbon nitride to 0.05-0.2:1, the electronic structure of crystalline carbon nitride can be precisely controlled, the reaction activity of graphite carbon nitride and peracetic acid can be improved, and the prepared manganese metal doped crystalline carbon nitride catalyst has better catalytic performance. At the same time, by optimizing the amount of manganese source, a catalyst with a suitable manganese metal doping content can be obtained, thereby enhancing the stability of the catalyst, improving its recycling performance, and extending the life of the catalyst. More importantly, by optimizing the amount of manganese source, the manganese metal active site occupies a dominant position in the manganese metal doped crystalline carbon nitride catalyst and actively participates in the catalytic process, thereby significantly improving the sensitivity of the catalyst to activate peracetic acid, and by efficiently activating peracetic acid, the ability to efficiently degrade organic pollutants is demonstrated. In particular, when the manganese metal doping concentration is too low, the catalytic active center will be too low, affecting the catalytic performance. When the manganese metal doping concentration is too high, the metal element will form a large number of metal clusters, affecting the stability and selectivity of the material. The formation of metal clusters may also affect the microstructure of the material, leading to lattice distortion, pore blockage and other problems, further affecting the physical and chemical properties of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention.
[0028] Figure 1Scanning electron microscope (SEM) images of monomeric carbon nitride (BCN), crystalline carbon nitride (CCN) and manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) prepared in Example 1 of the present invention.
[0029] Figure 2 Transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM) images of monomeric carbon nitride (BCN), crystalline carbon nitride (CCN) and manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) prepared in Example 1 of the present invention.
[0030] Figure 3 The X-ray diffraction (XRD) comparison patterns of the monomeric carbon nitride (BCN), crystalline carbon nitride (CCN) and manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) prepared in Example 1 of the present invention are shown.
[0031] Figure 4 Fourier transform infrared spectra of monomeric carbon nitride (BCN), crystalline carbon nitride (CCN) and manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) prepared in Example 1 of the present invention.
[0032] Figure 5 This is a time-degradation efficiency relationship diagram corresponding to the activation of peracetic acid and degradation of fluoroquinolone drug wastewater by monomeric carbon nitride (BCN), crystalline carbon nitride (CCN) and manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) in Example 1 of the present invention.
[0033] Figure 6 This is a time-degradation efficiency relationship diagram corresponding to the activation of peracetic acid and degradation of fluoroquinolone pharmaceutical wastewater by manganese metal-doped crystalline carbon nitride catalysts (MCCN0.5, MCCN1, MCCN1.5, MCCN2) with different manganese doping amounts in Example 1 of the present invention.
[0034] Figure 7 This is a graph showing the degradation effects under different ionic conditions when the manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) activates peracetic acid and degrades enrofloxacin wastewater in Example 2 of the present invention.
[0035] Figure 8 This is a graph showing the degradation effects under different pH conditions when the manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) activates peracetic acid and degrades enrofloxacin wastewater in Example 3 of the present invention.
[0036] Fig. 9This is a time-degradation efficiency relationship diagram corresponding to the activation of peracetic acid and degradation of naproxen pharmaceutical wastewater by monomeric carbon nitride (BCN), crystalline carbon nitride (CCN) and manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) in Example 4 of the present invention. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby.
[0038] In the following examples of the present invention, unless otherwise specified, the materials and instruments used are commercially available, the equipment used is conventional equipment, and the data obtained are the average values of more than three repeated experiments.
[0039] Example 1
[0040] A method for degrading organic pollutants by activating peracetic acid using a manganese metal-doped crystalline carbon nitride catalyst, specifically using a manganese metal-doped crystalline carbon nitride catalyst as a catalyst for activating peracetic acid to degrade fluoroquinolone drugs in water, comprising the following steps:
[0041] 5 mg of manganese metal-doped crystalline carbon nitride catalyst (MCCN0.5, MCCN1, MCCN1.5, MCCN2) with different manganese doping amounts was added to 100 mL of a 2 mg / L fluoroquinolone drug aqueous solution (simulated wastewater). Fluoroquinolone drugs are typical pollutants, namely enrofloxacin, norfloxacin, ofloxacin, and ciprofloxacin. The pH was adjusted to 7 using hydrochloric acid and sodium hydroxide solutions, and peracetic acid was added to make the concentration of peracetic acid in the wastewater 0.08 mmol / L. The fluoroquinolone drug aqueous solution was subjected to degradation reaction at 25°C for 6 minutes to complete the degradation of fluoroquinolone drugs in the wastewater.
[0042] Control group 1: Monomer carbon nitride (BCN) was used instead of manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5), and other conditions were the same.
[0043] Control group 2: Crystalline carbon nitride (CCN) was used instead of the manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5), and other conditions were the same.
[0044] Control group 3: only manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) was added, and other conditions were the same.
[0045] Control group 4: only peracetic acid (PAA) was added, and other conditions were the same.
[0046] In this embodiment, the manganese metal doped crystalline carbon nitride catalyst (MCCN0.5) includes crystalline carbon nitride, the crystalline carbon nitride is doped with manganese metal elements, and the crystalline carbon nitride is a flower-like nanosheet structure. The doping amount of manganese metal elements in the manganese metal doped crystalline carbon nitride catalyst (MCCN0.5) is 1.13wt%.
[0047] In this embodiment, the preparation method of the manganese metal-doped crystalline carbon nitride catalyst (MCCN0.5) includes the following steps:
[0048] S1. Using dicyandiamide as a raw material for polycondensation reaction, amorphous carbon nitride with a specific melon structure is obtained, as follows:
[0049] Take 5g of dicyandiamide and put it into a crucible, place it in a muffle furnace, heat it to 520℃ at a heating rate of 2℃ / min, and keep it at 520℃ for 4h. After natural cooling, take it out and grind it with a mortar to obtain a yellow powder sample, which is monomer carbon nitride (amorphous carbon nitride), recorded as BCN.
[0050] S2, pyrolyzing the amorphous carbon nitride obtained in step S1 to obtain crystalline carbon nitride, specifically as follows:
[0051] Take 2 g of BCN prepared in step S1 and place it in an alumina crucible porcelain boat. Completely wrap the alumina crucible porcelain boat containing the powder sample with aluminum foil, then place it in a tubular furnace and heat it to 620°C at a heating rate of 2°C / min under the protection of nitrogen. Keep it at 620°C for 2 h, take it out after natural cooling, and grind it with a mortar to obtain a yellow powder, which is crystalline carbon nitride, recorded as CCN.
[0052] S3. Grind and mix 1 g of the crystalline carbon nitride obtained in step S2 and 0.05 g of a manganese source (manganese chloride powder), place them in a tubular furnace, and heat them to 500°C at a heating rate of 5°C / min under an inert atmosphere. Calcined and kept at 500°C for 4 h, and then taken out after natural cooling to obtain a manganese metal-doped crystalline carbon nitride catalyst, recorded as MCCN0.5.
[0053] In this embodiment, the manganese metal doped crystalline carbon nitride catalyst (MCCN1) includes crystalline carbon nitride, the crystalline carbon nitride is doped with manganese metal elements, and the crystalline carbon nitride is a flower-like nanosheet structure. The doping amount of manganese metal elements in the manganese metal doped crystalline carbon nitride catalyst (MCCN1) is 2.23wt%.
[0054] In this embodiment, the preparation method of the manganese metal-doped crystalline carbon nitride catalyst (MCCN1) and the preparation method of the manganese metal-doped crystalline carbon nitride catalyst (MCCN0.5) are different only in that the amount of manganese source (manganese chloride powder) used in the preparation method of the manganese metal-doped crystalline carbon nitride catalyst (MCCN1) is 0.1 g.
[0055] In this embodiment, the manganese metal doped crystalline carbon nitride catalyst (MCCN1.5) includes crystalline carbon nitride, the crystalline carbon nitride is doped with manganese metal elements, and the crystalline carbon nitride is a flower-like nanosheet structure. The doping amount of manganese metal elements in the manganese metal doped crystalline carbon nitride catalyst (MCCN1.5) is 3.17wt%.
[0056] In this embodiment, the preparation method of the manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) used is different from the preparation method of the manganese metal-doped crystalline carbon nitride catalyst (MCCN0.5) in that the amount of manganese source (manganese chloride powder) used in the preparation method of the manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) is 0.15 g.
[0057] In this embodiment, the manganese metal doped crystalline carbon nitride catalyst (MCCN2) includes crystalline carbon nitride, the crystalline carbon nitride is doped with manganese metal elements, and the crystalline carbon nitride is a flower-like nanosheet structure. The doping amount of manganese metal elements in the manganese metal doped crystalline carbon nitride catalyst (MCCN2) is 4.87wt%.
[0058] In this embodiment, the preparation method of the manganese metal-doped crystalline carbon nitride catalyst (MCCN2) used is different from the preparation method of the manganese metal-doped crystalline carbon nitride catalyst (MCCN0.5) in that the amount of manganese source (manganese chloride powder) used in the preparation method of the manganese metal-doped crystalline carbon nitride catalyst (MCCN2) is 0.2 g.
[0059] The monomeric carbon nitride (BCN), crystalline carbon nitride (CCN) and manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) were subjected to electron microscope scanning.
[0060] Figure 1 Scanning electron microscope (SEM) images of monomeric carbon nitride (BCN), crystalline carbon nitride (CCN) and manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) prepared in Example 1 of the present invention. Figure 1 Among them, (a) is monomeric carbon nitride, (b) is crystalline carbon nitride, and (c) is manganese metal-doped crystalline carbon nitride catalyst.
[0061] Figure 2Transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM) images of monomeric carbon nitride (BCN), crystalline carbon nitride (CCN) and manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) prepared in Example 1 of the present invention. Figure 2 In the figure, (a) is a transmission electron microscopy image of monomer carbon nitride, (b) is a high-resolution transmission electron microscopy image of monomer carbon nitride, and (c) is a selected area electron diffraction image of monomer carbon nitride; (d) is a transmission electron microscopy image of crystalline carbon nitride, (e) is a high-resolution transmission electron microscopy image of crystalline carbon nitride, and (f) is a selected area electron diffraction image of crystalline carbon nitride; (g) is a transmission electron microscopy image of a manganese metal-doped crystalline carbon nitride catalyst, (h) is a high-resolution transmission electron microscopy image of a manganese metal-doped crystalline carbon nitride catalyst, and (i) is a selected area electron diffraction image of a manganese metal-doped crystalline carbon nitride catalyst.
[0062] from Figure 1 and Figure 2 It can be seen that the monomer carbon nitride presents a block-like aggregate structure without obvious lattice diffraction stripes. Crystalline carbon nitride and manganese metal-doped crystalline carbon nitride present a good flower-like morphology. High-resolution transmission electron microscopy shows that manganese metal-doped crystalline carbon nitride has obvious lattice stripes. Figure 2 e shows an apparent lattice spacing of 0.55 nm, which is attributed to the (100) plane of CCN. Figure 2 Clear lattice fringes were observed in h, and the shortened 0.32nm lattice fringes indicate the high crystallinity of MCCN1.5. The lattice fringes with lattice spacings of 0.32nm and 0.55nm correspond to the (002) and (100) planes of carbon nitride, respectively. In addition, combined with selected area electron diffraction (SAED), it was found that crystalline carbon nitride and manganese metal-doped crystalline carbon nitride had obvious diffraction spots, showing a ring pattern, indicating the polycrystalline nature of carbon nitride. The above results successfully verified the successful preparation of crystalline carbon nitride.
[0063] X-ray scanning was performed on monomeric carbon nitride (BCN), crystalline carbon nitride (CCN) and manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5).
[0064] Figure 3 The X-ray diffraction (XRD) comparison patterns of the monomeric carbon nitride (BCN), crystalline carbon nitride (CCN) and manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) prepared in Example 1 of the present invention are shown in FIG. Figure 3 It can be found that there are two obvious XRD diffraction peaks at 13° and 27°, which belong to the (100) and (002) crystal planes of graphite phase carbon nitride, confirming that the prepared product is gC 3 N 4. Compared with monomeric carbon nitride, the 27° peak of crystalline carbon nitride and manganese metal doped crystalline carbon nitride catalyst becomes narrower and the intensity becomes stronger, indicating that the crystallinity of carbon nitride is improved; in addition, compared with monomeric carbon nitride, the 13° peak of crystalline carbon nitride and manganese metal doped crystalline carbon nitride catalyst shifts to a low angle, corresponding to the increase in crystallinity. This proves the successful preparation of crystalline carbon nitride and manganese metal doped crystalline carbon nitride. Compared with the 27° peak of crystalline carbon nitride and manganese metal doped crystalline carbon nitride catalyst, the incorporation of Mn causes a slight change in the position and intensity of the (002) characteristic peak, an increase in the diffraction angle, and a decrease in the intensity, indicating that Mn is successfully embedded in the CCN skeleton.
[0065] The monomeric carbon nitride (BCN), crystalline carbon nitride (CCN) and manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) were analyzed by Fourier transform infrared spectroscopy.
[0066] Figure 4 The following are Fourier transform infrared spectra of monomeric carbon nitride (BCN), crystalline carbon nitride (CCN) and manganese metal doped crystalline carbon nitride catalyst (MCCN1.5) prepared in Example 1 of the present invention. Figure 4 As shown in Figure 2, the molecular structure of the sample was analyzed by Fourier transform infrared spectroscopy. The characteristic band of carbon nitride is between 1600 and 1200 cm -1 The skeletal vibration of the aromatic carbon nitride heterocycle is at 810 cm -1 The out-of-plane breathing mode of the triazine unit is at 3000-3500 cm -1 There are multiple broad peaks at 1600-1200cm-1 corresponding to the vibration of NH bonds. The Fourier transform infrared spectrum pattern remains basically unchanged after the introduction of manganese metal atoms, indicating that the introduction of manganese metal atoms does not change the basic structure of carbon nitride. -1 The intensity of the characteristic peak at gradually weakens compared with the original carbon nitride, which may be due to the chemical coordination of manganese element with triazine unit leading to the increase of amorphous carbon.
[0067] In this example, during the degradation reaction, 0.5 mL of wastewater was taken every 1 min, filtered, and 0.02 mL of 0.1 M sodium thiosulfate solution was added to terminate the reaction, and the remaining fluoroquinolone drug concentration was measured. The results are as follows: Figure 5 , 6 shown.
[0068] Figure 5 This is a time-degradation efficiency relationship diagram corresponding to the activation of peracetic acid and degradation of fluoroquinolone drug wastewater by monomeric carbon nitride (BCN), crystalline carbon nitride (CCN) and manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) in Example 1 of the present invention. Figure 5Among them, a is enrofloxacin wastewater; b is norfloxacin wastewater; c is ofloxacin wastewater; d is ciprofloxacin wastewater. Figure 5 It can be seen that manganese metal doped crystalline carbon nitride catalyst (MCCN1.5) can effectively activate peracetic acid to remove fluoroquinolone drugs in water. After 6 minutes of treatment, the degradation rates of enrofloxacin, norfloxacin, ofloxacin and ciprofloxacin aqueous solutions reached 100%, 97.9%, 94.3% and 98.1% respectively. Figure 5 It can be seen that adding only manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) or peracetic acid (PAA) cannot remove fluoroquinolone drugs in water, and the ability of BCN and CCN to activate peracetic acid is weak.
[0069] Figure 6 This is a time-degradation efficiency relationship diagram corresponding to the activation of peracetic acid and degradation of fluoroquinolone pharmaceutical wastewater by manganese metal-doped crystalline carbon nitride catalysts (MCCN0.5, MCCN1, MCCN1.5, MCCN2) with different manganese doping amounts in Example 1 of the present invention. Figure 6 Among them, a is enrofloxacin wastewater; b is norfloxacin wastewater; c is ofloxacin wastewater; d is ciprofloxacin wastewater. Figure 6 It can be seen that manganese metal-doped crystalline carbon nitride catalysts with different manganese doping amounts all showed strong peracetic acid activation ability, and showed strong removal ability for enrofloxacin, norfloxacin, ofloxacin and ciprofloxacin removal rates. Among them, MCCN1.5 has the strongest ability to activate peracetic acid to degrade pollutants. These results indicate that the Mn metal active sites occupy a dominant position in MCCN1.5 and actively participate in the catalytic process.
[0070] Example 2
[0071] A method for degrading organic pollutants by activating peracetic acid using a manganese metal-doped crystalline carbon nitride catalyst, specifically using the manganese metal-doped crystalline carbon nitride catalyst prepared in Example 1 as a catalyst for activating peracetic acid to degrade enrofloxacin in water, comprising the following steps:
[0072] 5 mg of the manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) prepared in Example 1 was added to 100 mL of an enrofloxacin aqueous solution (simulated wastewater) with a concentration of 2 mg / L. SO 4 2- NH 4 + , HCO 3 - , CO 3 - and Cl -, use hydrochloric acid and sodium hydroxide solution to adjust the pH to 7, add peracetic acid to make the concentration of peracetic acid in the wastewater be 0.08 mmol / L, and carry out degradation reaction on the enrofloxacin aqueous solution at 25°C for 6 minutes to complete the degradation of enrofloxacin in the wastewater.
[0073] In this example, during the degradation reaction, 0.5 mL of wastewater was taken every 1 min, filtered, and 0.02 mL of 0.1 M sodium thiosulfate solution was added to terminate the reaction, and the remaining enrofloxacin concentration was measured. The results are as follows: Figure 7 shown.
[0074] Figure 7 This is a graph showing the degradation effects under different ionic conditions when the manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) activates peracetic acid and degrades enrofloxacin wastewater in Example 2 of the present invention. Figure 7 In the figure, the ordinate is the degradation efficiency of enrofloxacin at a certain moment, which is calculated by dividing the concentration of degraded enrofloxacin at that moment by the value of the initial concentration of enrofloxacin. Figure 7 It can be seen from the figure that the manganese metal-doped crystalline carbon nitride catalyst prepared in the present invention is stable in deionized water and in a medium containing SO 4 2- NH 4 + , HCO 3 - , CO 3 - and Cl - The removal rate of enrofloxacin was almost not affected in the water body, and efficient catalytic performance was shown. This indicates that the manganese metal-doped crystalline carbon nitride catalyst of the present invention has excellent anti-interference ability when activating peracetic acid and has good practical applicability.
[0075] Example 3
[0076] A method for degrading organic pollutants by activating peracetic acid using a manganese metal-doped crystalline carbon nitride catalyst, specifically using the manganese metal-doped crystalline carbon nitride catalyst prepared in Example 1 as a catalyst for activating peracetic acid to degrade enrofloxacin in water, comprising the following steps:
[0077] 5 mg of the manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) prepared in Example 1 was added to 100 mL of an enrofloxacin aqueous solution (simulated wastewater) with a concentration of 2 mg / L, and the pH was adjusted to 3, 5, 7, 9, and 11 using hydrochloric acid and sodium hydroxide solutions. Peracetic acid was added to a concentration of 0.08 mmol / L in the wastewater, and the enrofloxacin aqueous solution was subjected to a degradation reaction at 25°C for 6 minutes to complete the degradation of enrofloxacin in the wastewater.
[0078] In this example, during the degradation reaction, 0.5 mL of wastewater was taken every 1 min, filtered, and 0.02 mL of 0.1 M sodium thiosulfate solution was added to terminate the reaction, and the remaining enrofloxacin concentration was measured. The results are as follows: Figure 8 shown.
[0079] Figure 8 This is a graph showing the degradation effects under different pH conditions when the manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) activates peracetic acid and degrades enrofloxacin wastewater in Example 3 of the present invention. Figure 8 In the figure, the ordinate is the degradation efficiency of enrofloxacin at a certain moment, which is calculated by dividing the concentration of degraded enrofloxacin at that moment by the value of the initial concentration of enrofloxacin. Figure 8 It can be seen that the manganese metal-doped crystalline carbon nitride catalyst prepared by the present invention shows a high removal rate for enrofloxacin under a wide range of pH values, and only slightly inhibits the degradation of enrofloxacin in a relatively acidic environment (pH=3) or a relatively alkaline environment (pH=11), which indicates that the manganese metal-doped crystalline carbon nitride catalyst prepared by the present invention has strong acid-base tolerance.
[0080] Example 4
[0081] A method for degrading organic pollutants by activating peracetic acid using a manganese metal-doped crystalline carbon nitride catalyst, specifically using the manganese metal-doped crystalline carbon nitride catalyst prepared in Example 1 as a catalyst for activating peracetic acid to degrade naproxen in water, comprising the following steps:
[0082] 5 mg of the manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) prepared in Example 1 was added to 100 mL of a 2 mg / L naproxen drug aqueous solution (simulated wastewater), the pH was adjusted to 7 using hydrochloric acid and sodium hydroxide solutions, peracetic acid was added to a concentration of 0.08 mmol / L in the wastewater, and the naproxen drug aqueous solution was subjected to a degradation reaction at 25° C. for 6 minutes to complete the degradation of the naproxen drug in the wastewater.
[0083] Control group 1: Monomer carbon nitride (BCN) was used instead of manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5), and other conditions were the same.
[0084] Control group 2: Crystalline carbon nitride (CCN) was used instead of the manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5), and other conditions were the same.
[0085] Control group 3: only manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) was added, and other conditions were the same.
[0086] Control group 4: only peracetic acid (PAA) was added, and other conditions were the same.
[0087] In this example, during the degradation reaction, 0.5 mL of wastewater was taken every 1 min, filtered, and 0.02 mL of 0.1 M sodium thiosulfate solution was added to terminate the reaction, and the remaining naproxen drug concentration was measured. The results are as follows: Fig. 9 shown.
[0088] Fig. 9 The figure is a time-degradation efficiency relationship diagram corresponding to the activation of peracetic acid and degradation of naproxen pharmaceutical wastewater by monomeric carbon nitride (BCN), crystalline carbon nitride (CCN) and manganese metal-doped crystalline carbon nitride catalyst (MCCN1.5) in Example 4 of the present invention. Fig. 9 It can be seen that manganese metal doped crystalline carbon nitride catalyst can efficiently activate peracetic acid and remove naproxen in water. After 6 minutes of treatment, the degradation rate of naproxen reached 96.8%. In addition, the results show that only adding manganese metal doped crystalline carbon nitride catalyst (MCCN1.5) or peracetic acid (PAA) cannot remove naproxen in water, and the ability of BCN and CCN to activate peracetic acid is weak.
[0089] From the above results, it can be seen that in the method of the present invention for activating peracetic acid to degrade organic pollutants using a manganese metal-doped crystalline carbon nitride catalyst, the manganese metal-doped crystalline carbon nitride catalyst used has higher crystallinity, more active sites, and higher catalytic activity. Therefore, when it is used as a catalyst for activating peracetic acid, it can achieve efficient activation of peracetic acid and quickly form a large amount of highly active substances, and then these highly active substances can be used to efficiently oxidize and decompose organic pollutants to achieve efficient degradation of organic pollutants. Taking fluoroquinolone drugs as an example, at 25° C. and an initial solution pH value of 7.0, only 5 mg of catalyst and 0.08 mmol of peracetic acid are needed to degrade 100 mL, 2 mg / L of enrofloxacin, norfloxacin, ofloxacin, and ciprofloxacin aqueous solutions within 6 minutes by 100%, 97.9%, 94.3%, and 98.1%, respectively. The method has the advantages of small catalyst dosage, low cost, high treatment efficiency, good removal effect, and green environmental protection, and is of great significance for effectively removing organic pollutants in the environment.
[0090] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for degrading organic pollutants by activating peracetic acid using a manganese metal-doped crystalline carbon nitride catalyst, characterized in that: The method uses a manganese metal-doped crystalline carbon nitride catalyst as a catalyst for activating peracetic acid to degrade organic pollutants; the manganese metal-doped crystalline carbon nitride catalyst comprises crystalline carbon nitride, and the crystalline carbon nitride is doped with manganese metal elements.
2. The method according to claim 1, characterized in that The doping amount of manganese metal element in the manganese metal doped crystalline carbon nitride catalyst is 1.13% to 4.87%; the crystalline carbon nitride is a flower-shaped nanosheet.
3. The method according to claim 2, characterized in that The method for preparing the manganese metal-doped crystalline carbon nitride catalyst comprises the following steps: S1, using a nitrogen precursor as a raw material to carry out a polycondensation reaction to obtain amorphous carbon nitride; S2, pyrolyzing the amorphous carbon nitride obtained in step S1 to obtain crystalline carbon nitride; S3, grinding and mixing the crystalline carbon nitride and the manganese source obtained in step S2, and then calcining them to obtain a manganese metal-doped crystalline carbon nitride catalyst.
4. The method according to claim 3, characterized in that In step S3, the mass ratio of the manganese source to the crystalline carbon nitride is 0.05-0.2:
1.
5. The method according to claim 4, characterized in that In step S3, the mass ratio of the manganese source to the crystalline carbon nitride is 0.1-0.2:1; and the manganese source is manganese chloride.
6. The method according to claim 5, characterized in that In step S1, the nitrogen precursor is at least one of dicyandiamide, melamine and urea; the polycondensation reaction is carried out under a protective atmosphere; the protective atmosphere is air or nitrogen; the heating rate during the polycondensation reaction is 2°C / min to 10°C / min; the polycondensation reaction is carried out at a temperature of 500°C to 600°C; the polycondensation reaction time is 4h to 6h; In step S2, the pyrolysis treatment is carried out under a protective atmosphere; the protective atmosphere is nitrogen; the heating rate during the pyrolysis treatment is 2°C / min to 10°C / min; the pyrolysis treatment is carried out at a temperature of 500°C to 700°C; and the pyrolysis treatment time is 2h to 4h; In step S3, the calcination is carried out under a protective atmosphere; the protective atmosphere is nitrogen; the heating rate during the calcination is 2°C / min to 10°C / min; the calcination temperature is 500°C to 600°C; and the calcination time is 4h to 6h.
7. The method according to any one of claims 1 to 6, characterized in that: Organic pollutants in water bodies are degraded using manganese metal-doped crystalline carbon nitride catalyst as a catalyst for activating peracetic acid.
8. The method according to claim 7, characterized in that When organic pollutants in water are degraded by using a manganese metal-doped crystalline carbon nitride catalyst as a catalyst for activating peracetic acid, the method comprises the following steps: mixing the manganese metal-doped crystalline carbon nitride catalyst and organic pollutant wastewater, adding peracetic acid to carry out a degradation reaction, and completing the degradation of the organic pollutants in the wastewater; the addition amount of the manganese metal-doped crystalline carbon nitride catalyst is 0.05 g to 0.1 g per liter of organic pollutant wastewater; and the addition amount of the peracetic acid is 0.05 mmol to 0.1 mmol per liter of organic pollutant wastewater.
9. The method according to claim 8, characterized in that The organic pollutants in the organic pollutant wastewater are antibiotics or naproxen drugs; the antibiotics are fluoroquinolone drugs; the fluoroquinolone drugs are at least one of enrofloxacin, norfloxacin, ofloxacin, and ciprofloxacin; the initial concentration of organic pollutants in the organic pollutant wastewater is 2 mg / L to 5 mg / L; the pH value of the organic pollutant wastewater is 5.0 to 7.
0.
10. The method according to claim 9, characterized in that The degradation reaction is carried out at a temperature of 25°C to 30°C; the degradation reaction time is 3min to 10min.
Citation Information
Patent Citations
Preparation method and application of ball-flower-shaped Bi2WO6 loaded sulfur-doped porous carbon nitride composite photocatalyst
CN118002174A